Yonyou 2013 - McFarlan, F. Warren (Franklin Warren); Zheng, Xiaoming; Zhao, Ziqian ([London] : SAGE, 2016)
In January 2013, Yonyou Software, the largest management software company in Asia-Pacific, unfolded its three-year business strategy to step up platform development. Following its decade earlier transition from financial software to management software, Yonyou's three-year business strategy was again a business model revolution. This book details Yonyou's plans.
Originally Published in: McFarlan, F. W., Zheng, X. & Zhao, Z. (2014). Yonyou 2013. 0-314-331. Beijing: Tsinghua SEM China Business Case Center.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Yonyou Software (Firm); Business planning -- Case studies; Strategic planning -- Case studies